Kinematic estimation of fracture mechanics parameter with automatic crack-tip identification. (January 2022) - Baldi, Antonio; Santucci, Pietro Maria
Abstract: Digital Image Correlation (DIC) is probably one of the most used optical methods for displacements and strains measurement and has been used both in its standard form and in its integrated variant to extract the fracture mechanics parameters from a set of images of the crack. However, differently from photoelasticity, where stress data is directly available because the imaged fringes are proportional to σ 1 − σ 2, in the DIC case the fracture mechanics parameters result from a reverse calibration procedure involving the least-squares fit of a theoretical displacement model to the experimental data. Thus, the accuracy of the computed parameters critically depends on the exact identification of the crack location and orientation. This problem is well known, and a partial solution has been provided by Réthoré et al. (2008), who proposed an approach for computing the distance from the estimated and the true location of the crack tip in the longitudinal direction using the first hypersingular functions (i.e., the 1st negative term of William's series). However, no hint is provided to estimate the crack orientation. This work wants to fill the gap, describing an automatic algorithm for the complete identification of the crack tip location. Highlights: Two automatic algorithms for crack tip location are proposed. The use of supersingular fields is extended to allow for a complete crack location. Subsingular fields give a marginal contribution to stress parameters identification. Crack Orientation is shown to be a critical parameter. Image generator for iDIC testing is described.